Inflammation Is More Sensitive than Cell Proliferation in Response to Rapamycin Treatment in Polycystic Kidney Disease - Ming Yang; Jiayi Lv; Chanjuan Gong; Cheng Xue; Lili Fu; Shunjie Chen; Changlin Mei (Karger Publishers, 2024)
Introduction: It has been reported that rapamycin inhibited inflammation in renal interstitial diseases. We therefore hypothesized that rapamycin could attenuate inflammation in polycystic kidney disease (PKD). Methods: Han:SPRD rats were treated with rapamycin by daily gavage from 4 weeks to 12 weeks of age at the dosage of 0.5 mg/kg/day (low dose) or 1 mg/kg/day (high dose). WT9-12 human PKD cells were treated with various concentrations of rapamycin. Results: Two-kidney/total body weight ratio and cystic index in Cy/+ kidneys were significantly reduced with the treatment of low-dose rapamycin and further reduced by the treatment with high-dose rapamycin. However, the renal function of Cy/+ rats was equally improved by the treatment with either low-dose or high-dose rapamycin. The renal cell proliferation was significantly decreased in Cy/+ kidneys with the treatment of low-dose rapamycin and was further decreased with the treatment of high-dose rapamycin as examined by Ki67 staining. The phosphorylation of S6K in cystic kidneys was decreased by low-dose rapamycin and further decreased by high-dose rapamycin. Both low-dose and high-dose rapamycin treatment decreased macrophage infiltration and the expression of complement factor B (CFB), monocyte chemoattractant protein-1 (MCP-1), and tumor necrosis factor-alpha (TNF-α) to a similar level. The expression of CFB, MCP-1, and TNF-α and phosphorylation of S6K were inhibited in WT9-12 cells treated with 10 nm rapamycin at 24 h and 48 h, respectively. Moreover, the phosphorylation of Akt was not increased by 1 nm and 10 nm of rapamycin and enhanced by 1 μm rapamycin treatment. Interestingly, WT9-12 cell proliferation could be inhibited by 1 μm rapamycin. Conclusion: Low dose of rapamycin could inhibit inflammation and protect renal function in PKD. Inflammation is more sensitive than cell proliferation in response to rapamycin treatment in PKD.